2020
DOI: 10.1108/sef-01-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: external driver of the cryptocurrency world

Abstract: Purpose Considering the different motivation for the creation of each of these cryptocurrencies, the purpose of this paper is to examine whether there is a dominant external factor in the cryptocurrency world. Using a novel two-step time and frequency independent methodology, the authors examine a large scope of cryptocurrencies and external factors within the same period, and analytical framework. Design/methodology/approach The examined cryptocurrencies are Bitcoin, Ethereum, Ripple, Litecoin, Monero and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Few studies pointed out rising dominance of bitcoin makes reset the support level of Altcoins [28] and observed progress in the price movement of Altcoins when the dominance of bitcoin is decreased [29] . The crypto market showed explosive behaviour among cryptocurrencies except for NEM coin, which supported the earlier literature [5,10,22,30,31] .…”
Section: Review Of Literaturesupporting
confidence: 89%
“…Few studies pointed out rising dominance of bitcoin makes reset the support level of Altcoins [28] and observed progress in the price movement of Altcoins when the dominance of bitcoin is decreased [29] . The crypto market showed explosive behaviour among cryptocurrencies except for NEM coin, which supported the earlier literature [5,10,22,30,31] .…”
Section: Review Of Literaturesupporting
confidence: 89%
“…The presence of corporations in the cryptocurrency market was also not felt until mid-2020s when the various financial institution began investing in bitcoin by holding them on their balance sheets (Erzurumlu, Oygur & Kirik, 2020). A recent survey by the CoinDesk revealed that in 2020, the largest institutional holder of Bitcoins was the merchant bank Galaxy Digital Holdings in US which held 16,400 BTC which were worth $357 million.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that six major cryptocurrencies do provide diversification benefits, as they show no signs of integration with equity and Forex markets. Each coin acts as an independent character, therefore indexes such as S&P500, NASDAQ, NIKKEI225 and Shanghai hold no influence on the price changes of cryptocurrencies (Erzurumlu et al , 2020). In general, cryptocurrencies share characteristics with traditional financial instruments but they function independently and uninfluenced by their trends.…”
Section: Introductionmentioning
confidence: 99%